Jason Interpreter, Enterprise Edition (Informatica, 2016)
The Enterprise edition of the Java platform has been endorsed by both small and largeenterprises, as it enables the development of large-scale, reliable, and secure softwaresolutions. In the world of agent development, on the other hand, AgentSpeak, and itspractical interpreter Jason, represent one of the most popular tools for writing complex,reasoning agents. This paper presents a framework that integrates the two approaches todistributed software development, and supports a seamless deployment of Jason agentsin enterprise environments. The proposed framework o ers many technical advantages,including automated agent load-balancing and fault-tolerance. The end-goal of thisresearch, however, is to try and bridge the gap between the agent technology and modernenterprise applications.